Quadratic performance analysis of switched affine time-varying systems - Li, Wenzhi; Huang, Chi; Zhai, Guisheng (Zielona Góra: Uniwersytet Zielonogórski)
We analyze quadratic performance for switched systems which are composed of a finite set of affine time-varying subsystems, where both subsystem matrices and affine vectors are switched, and no single subsystem has desired quadratic performance. The quadratic performance indexes we deal with include stability, tracking and L2 gain.
Keywords: switched affine systems; time-varying systems; quadratic stabilization; tracking; L2 gain; switching law; differential LMIs; observers